Cholinergic regulation along the pulmonary arterial tree of the South American rattlesnake: vascular reactivity, muscarinic receptors, and vagal innervation - Filogonio, Renato; Sartori, Marina R. [UNESP]; Morgensen, Susie; Tavares, Driele; Campos, Rafael; Abe, Augusto S. [UNESP]; Taylor, Edwin W.; Rodrigues, Gerson J.; De Nucci, Gilberto; Simonsen, Ulf; Leite, Cleo A. C.; Wang, Tobias (Amer Physiological Soc, 2020)
Vascular tone in the reptil-ian pulmonary vasculature is primarily under cholinergic, muscarinic control exerted via the vagus nerve. This control has been ascribed to a sphincter located at the arterial outflow, but we speculated whether the vascular control in the pulmonary artery is more widespread, such that responses to acetylcholine and electrical stimulation, as well as the expression of muscarinic receptors, are prevalent along its length. Working on the South American rattlesnake (Crotalus durissus), we studied four different portions of the pulmonary artery (truncus, proximal, distal, and branches). Acetylcholine elicited robust vaso-constriction in the proximal, distal, and branch portions, but the truncus vasodilated. Electrical field stimulation (EFS) caused contrac-tions in all segments, an effect partially blocked by atropine. We identified all five subtypes of muscarinic receptors (M1-M5). The expression of the M1 receptor was largest in the distal end and branches of the pulmonary artery, whereas expression of the musca-rinic M3 receptor was markedly larger in the truncus of the pulmonary artery. Application of the neural tracer 1,1'-dioctadecyl-3,3,3',3'- tetramethylindo-carbocyanine perchlorate (DiI) revealed widespread innervation along the whole pulmonary artery, and retrograde trans-port of the same tracer indicated two separate locations in the brainstem providing vagal innervation of the pulmonary artery, the medial dorsal motor nucleus of the vagus and a ventro-lateral location, possibly constituting a nucleus ambiguus. These results revealed parasympathetic innervation of a large portion of the pulmonary artery, which is responsible for regulation of vascular conductance in C. durissus, and implied its integration with cardiorespiratory control.
Keywords: cardiorespiratory integration; electrical field stimulation; intracardiac shunts; respiratory sinus arrythmia; vagus nerve